Calibração de um termômetro de carvão para o intervalo entre \'0,3 GRAUS K\' e \'20 GRAUS K\' - Frossati, Giorgio (1969)
Calibração de um termômetro de carvão para o intervalo entre \'0,3 GRAUS K\' e \'20 GRAUS K\'